Three‐Dimensional Broadband Interferometric Mapping and Polarization (BIMAP‐3D) Observations of Lightning Discharge Processes. Issue 4 (15th February 2023) - Shao, Xuan‐Min; Jensen, Daniel; Ho, Cheng; Graham, Paul; Haynes, William; Caffrey, Michael; Raby, Eric; Meierbachtol, Collin; Hemsing, David; Sonnenfeld, Richard
Abstract: Following on our earlier single‐station, 2‐dimensional (2D) broadband interferometric mapping and polarization (BIMAP) observations of lightning discharges, we recently deployed two BIMAP stations at Los Alamos National Laboratory to map the lightning sources and their polarization in full 3‐dimensional (3D) space (BIMAP‐3D). The two stations are separated by 11.5‐km and each station consists of four antenna sets (instead of three for the original BIMAP) that form a Y ‐shaped array for improved interferometric performance. In this paper, we report the BIMAP‐3D system design, a generalized and analytical 2D interferometry technique for noncoplanar antenna array, a two‐stage 3D mapping technique based on geometric triangulation and baseline‐based differential time of arrival, and a technique to reconstruct the polarization orientation in 3D space by combining the 2D polarization results from the two‐station observations. Along with description of the techniques, we demonstrate and discuss the initial lightning results, including 3D maps for a hybrid intracloud and cloud‐to‐ground flash and for a normal intracloud flash, development of abnormal K‐change leaders, and polarization signatures for a K‐change leader. We find that with the two‐stage 3D mapping techniques, the sources can be located to meters accuracy for a favorable event that occurs between the two stations. We also find the polarization vectors for the example K leader are mostly orthogonal to the leader channel after the full 3D polarization analysis. The main purpose of this paper is to report the BIMAP‐3D techniques and capabilities. Detailed analysis of more specific discharge processes will be reported in later studies. Plain Language Summary: A new 3‐dimensional broadband radio frequency interferometric mapping and polarization system (BIMAP‐3D) is developed and deployed at Los Alamos National Laboratory for lightning research. BIMAP‐3D provides an unprecedented capability in high‐resolution, time‐evolving 3D lightning source mapping and 3D source polarization detection for detailed study of lightning discharge physics. In this research, we described the BIMAP‐3D system, introduced a suite of advanced data processing techniques, and demonstrated BIMAP‐3D's capabilities with actual lightning observations. This new capability is expected to lead to a range of new understandings and discoveries for a variety of lightning discharge processes. Key Points: A new 3D broadband interferometric mapping and polarization system for lightning study is introduced A suite of new data process algorithms is reported, and 3D lightning results for overall flashes and K‐change leaders are demonstrated Polarization orientations for a K‐change leader are found mostly orthogonal to the leader channel